EFFECTIVENESS OF SCHOOL BASED MANAGEMENT TO IMPROVING QUALITY - Yahfizham Yahfizham; Salamuddin Salamuddin; Kun Perdana Lubis (Universitas Islam Negeri (UIN) Sumatera Utara, 2019)
The data are analyzed with an interactive model that is divided intodata collection, data reduction, data presentation, and drawing conclusions. Basedon. the results of research on the effectiveness of school-based management inimproving quality at Madrasah Ibtidaiyah Negeri Binjai City, so it can beconcluded that the effectiveness of MBS in MIN city of binjai can improve thequality of education. This can be seen from the interest of students entering thisschool and the achievements that have been made.